Nanoparticles for microbial control in water: mechanisms, applications, and ecological implications - Olawade, David B.; Wada, Ojima Z.; Fapohunda, Oluwaseun; Egbewole, Bamise I.; Ajisafe, Olawale; Ige, Abimbola O. (Frontiers in Nanotechnology, 2024)
Waterborne microbial contamination poses significant threats to public health and environmental sustainability. Traditional water treatment methods, while effective to a certain extent, are often limited in their ability to completely eradicate microbial pathogens and mitigate emerging challenges such as disinfection by-products and microbial resistance. In recent years, nanoparticles have emerged as promising candidates for microbial control in water treatment due to their unique physicochemical properties and antimicrobial efficacy. This review provides a comprehensive examination of the use of nanoparticles for microbial control in water treatment, focusing on their antimicrobial mechanisms, applications, and ecological implications. The review discusses the types of nanoparticles commonly used in water treatment, including silver nanoparticles, copper nanoparticles, titanium dioxide nanoparticles, and carbon-based nanoparticles, and examines their antimicrobial mechanisms, such as cell membrane damage, reactive oxygen species generation, and interference with microbial metabolic processes. Furthermore, the review explores the applications of nanoparticles in the disinfection of drinking water, wastewater treatment, water purification in remote areas, and biofilm control. Additionally, the ecological implications of nanoparticle-based water treatment, including nanoparticle release into the environment, environmental persistence, toxicity to non-target organisms, and regulatory challenges, are critically evaluated. Finally, future perspectives and challenges in nanoparticle-based water treatment, such as enhanced nanoparticle synthesis and stability, development of sustainable treatment technologies, integration with conventional methods, and addressing knowledge gaps, are discussed. Overall, this review provides valuable insights into the potential of nanoparticles as innovative tools for addressing microbial contamination in water treatment while highlighting the need for further research and sustainable practices to ensure their safe and effective implementation.